Polishing Pad

The polishing pad with a non-alicyclic diisocyanate and hygroscopic polymer composition addresses the balance of polishing rate, planarization, and scratch resistance, offering improved CMP performance.

JP7611411B2Active Publication Date: 2025-01-09KURARAY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023549765
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-27
Filing Date
2022-09-22
Publication Date
2025-01-09
Estimated Expiration
2042-09-22

AI Technical Summary

Technical Problem

Existing polishing pads struggle to balance high polishing rate, high flattening properties, low scratch properties, and excellent dressing properties, with concerns of scratches due to large particle sizes and compatibility issues in polyurethane compositions.

Method used

A polishing pad with a polyurethane composition containing 90 to 99.9% non-alicyclic diisocyanate units and 0.1 to 10% hygroscopic polymer, optimized for high D hardness, moisture absorption, and compatibility, forming a non-foamed molded body with specific mechanical properties.

Benefits of technology

The polishing pad achieves high polishing rate, excellent planarization, low scratch resistance, and improved dressing properties, with enhanced durability and efficiency in chemical mechanical polishing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611411000003
    Figure 0007611411000003
  • Figure 0007611411000001
    Figure 0007611411000001
  • Figure 0007611411000002
    Figure 0007611411000002
Patent Text Reader

Abstract

A polishing pad including a polishing layer that is a molded product of a polyurethane composition, in which the polyurethane composition comprises 90 to 99.9% by mass of a thermoplastic polyurethane containing a non-alicyclic diisocyanate unit as an organic diisocyanate unit, and 0.1 to 10% by mass of a hygroscopic polymer, and the molded product has a hardness of 75 to 90 when measured with a type-D durometer in accordance with JIS K 7215.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing pad, and more particularly to a polishing pad for polishing semiconductor wafers, semiconductor devices, silicon wafers, hard disks, glass substrates, optical products, various metals, and the like. [Background technology]

[0002] Chemical mechanical polishing (hereinafter also referred to as "CMP") is known as a polishing method used for mirror finishing of semiconductor wafers used as substrates for forming integrated circuits, and for flattening unevenness of insulating films and conductor films of semiconductor devices. CMP is a method of polishing the surface of a substrate to be polished, such as a semiconductor wafer, with a polishing pad using a polishing slurry (hereinafter also simply referred to as slurry) containing abrasive grains and a reactive liquid.

[0003] In CMP, the polishing results vary greatly depending on the properties and characteristics of the polishing layer of the polishing pad. For example, a soft polishing layer reduces scratches, which are polishing defects that occur on the polished surface, but reduces the local planarization and polishing speed of the polished surface. Also, a hard polishing layer improves the planarization of the polished surface, but increases the number of scratches that occur on the polished surface.

[0004] In addition, in CMP, the polishing result varies greatly depending on the surface roughness of the polishing surface of the polishing layer. By controlling the surface roughness of the polishing surface and improving the retention of the slurry, the polishing speed and the planarization of the surface to be polished can be improved. Furthermore, by making the surface roughness uniform, the polishing uniformity can be controlled. Furthermore, by improving the dressing property of the polishing surface, the dressing time for obtaining the optimum surface roughness in preparation for polishing can be shortened, shortening the process time and extending the life of the polishing pad.

[0005] Polyurethane is used as a material for the polishing layer having such various properties, and various improvements to polyurethane have been proposed.

[0006] For example, the following Patent Document 1 discloses a polishing pad having a polishing layer formed by dispersing a polymer containing an ether bond in the main chain, such as polyoxyethylene, and water-soluble particles, such as cyclodextrin, in a polymer matrix material, such as a conjugated diene copolymer. Patent Document 1 also discloses that such a polishing pad provides a high polishing rate, sufficiently suppresses the occurrence of scratches on the polished surface, and furthermore, can realize a high degree of uniformity in the polished surface with respect to the amount of polishing.

[0007] Also, the following Patent Document 2 discloses a chemical mechanical polishing pad having a polishing layer formed from a composition containing 80 to 99 parts by mass of thermoplastic polyurethane and 1 to 20 parts by mass of a polymer compound such as polyoxyethylene having a water absorption rate of 3 to 3000%. Patent Document 2 discloses that such a polishing pad forms pores by releasing water-soluble particles that come into contact with the slurry, and holds the slurry in the formed pores, thereby maintaining high planarization and reducing the occurrence of scratches.

[0008] In addition, the following Patent Document 3 discloses a polishing pad having a polishing layer containing first particles such as resin and calcium carbonate particles, and the first particles have an average particle diameter D 50 Patent Document 3 discloses a polishing pad in which the diameter of the first particles is 1.0 to less than 5.0 μm, the content of the first particles in the entire polishing layer is 6.0 to 18.0 volume %, and the Mohs hardness of the first particles is less than the Mohs hardness of the substrate to be polished. Patent Document 3 discloses that in such a polishing pad, the interface between the resin and the first particles becomes brittle, thereby obtaining excellent dressability. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2007 / 089004 [Patent Document 2] JP 2011-151373 A [Patent Document 3] JP 2019-155507 A Summary of the Invention [Problem to be solved by the invention]

[0010] With the polishing pads disclosed in Patent Documents 1 and 2, it was difficult to achieve a high polishing rate, high planarization, low scratch resistance, and excellent dressability. With the polishing pad disclosed in Patent Document 3, the particle diameter of the first particles was relatively large, so there was concern that scratches would be easily generated. Thus, with a polishing layer containing polyurethane, it was difficult to achieve a high polishing rate, high planarization, low scratch resistance, and excellent dressability.

[0011] An object of the present invention is to provide a polishing pad which combines a high polishing rate, high planarization properties, low scratch properties, and excellent dressability. [Means for solving the problem]

[0012] One aspect of the present invention is a polishing pad including a polishing layer that is a molded article of a polyurethane composition, the polyurethane composition containing 90 to 99.9 mass % of a thermoplastic polyurethane containing non-alicyclic diisocyanate units as organic diisocyanate units, and 0.1 to 10 mass % of a hygroscopic polymer having a moisture absorption rate of 0.1% or more. The thermoplastic polyurethane contains at least one non-alicyclic diisocyanate unit selected from 2,4'-diphenylmethane diisocyanate unit, 4,4'-diphenylmethane diisocyanate unit and hexamethylene diisocyanate unit in an amount of 90 to 100 mol % in the total amount of organic diisocyanate units. The hygroscopic polymer contains at least one selected from polyethylene oxide (PEO), polypropylene oxide (PPO), PEO-PPO block copolymer, polyester thermoplastic elastomer and polyethylene oxide-polypropylene oxide copolymer. The molded product is a polishing pad having a D hardness of 75 to 90, measured under conditions of a load holding time of 5 seconds using a type D durometer conforming to JIS K 7215. Such a polishing pad provides a high polishing rate, high planarization properties, low scratch properties, and excellent dressability.

[0013] The thermoplastic polyurethane preferably contains 90 to 100 mol % of 4,4'-diphenylmethane diisocyanate units, which are non-alicyclic diisocyanate units, in the total amount of organic diisocyanate units. In such a case, the hygroscopic polymer is easily dispersed in the thermoplastic polyurethane with particularly good compatibility.

[0014] The polyurethane composition preferably contains 99 to 99.9% by mass of thermoplastic polyurethane and 0.1 to 1% by mass of hygroscopic polymer, which makes it easier for the polishing layer to maintain a high D hardness and higher planarization properties.

[0015] Examples of hygroscopic polymers include polyethylene oxide and polyethylene oxide-propylene oxide block copolymers.

[0016] The molded article preferably has a breaking elongation of 50 to 250% when saturated and swollen with water at 50° C. In such a case, the polishing surface of the polishing layer becomes rougher while maintaining high planarization properties, and the dressability is improved.

[0017] The molded article preferably has a breaking elongation in a dry state of 0.1 to 10% at a humidity of 48 RH% and 23° C. In such a case, the polishing layer is more likely to retain higher planarization properties.

[0018] Furthermore, the molded article preferably has a ratio S1 / S2 of the breaking elongation S1 at saturated swelling to the breaking elongation S2 at dry condition of 20 to 50. In such a case, it becomes easier to obtain a polishing layer that is particularly excellent in dressability and flattenability.

[0019] Moreover, the molded product preferably has a laser light transmittance of 60% or more at a wavelength of 550 nm when a sheet having a thickness of 0.5 mm is saturated and swollen in water at 50° C. In such a case, a polishing layer having excellent low scratch resistance and easy to employ an inspection using an optical detection means for determining the polishing end point while polishing the polishing surface of a substrate such as a wafer can be easily obtained.

[0020] The molded article preferably has a Vickers hardness of at least 21. In such a case, it is easy to obtain a polishing layer that is particularly excellent in planarization properties.

[0021] The molded article preferably has a storage modulus of 0.1 to 1.0 GPa when swelled to saturation in water at 50° C. In such a case, it becomes easier to obtain a polishing layer that is more likely to retain higher flattening properties.

[0022] In addition, the molded body is preferably a non-foamed molded body.In this case, the hardness of the polishing layer is easily increased, so that it is easy to realize higher flatness and high polishing speed.In addition, the abrasive grains in the slurry are unlikely to enter into pores to form agglomerates of abrasive grains, so that the scratches caused by the agglomerates scratching the wafer surface are unlikely to occur. Effect of the Invention

[0023] According to the present invention, a polishing pad can be obtained that combines a high polishing rate, high planarization properties, low scratch properties, and excellent dressability. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is an explanatory diagram for explaining CMP using a polishing pad 10 of an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] An embodiment of the polishing pad will be described in detail below.

[0026] The polishing pad of this embodiment includes a polishing layer that is a molded product of a polyurethane composition. The polyurethane composition contains 90 to 99.9 mass% of a thermoplastic polyurethane containing a non-alicyclic diisocyanate unit as an organic diisocyanate unit (hereinafter also referred to as a non-alicyclic thermoplastic polyurethane) and 0.1 to 10 mass% of a hygroscopic polymer. The molded product has a D hardness of 75 to 90, measured with a type D durometer conforming to JIS K 7215 under the condition of a load retention time of 5 seconds.

[0027] A non-alicyclic thermoplastic polyurethane is a thermoplastic polyurethane obtained by reacting polyurethane raw materials including an organic diisocyanate, a polymer diol, and a chain extender. A non-alicyclic thermoplastic polyurethane is a thermoplastic polyurethane obtained by using an organic diisocyanate including a non-alicyclic diisocyanate. The proportion of non-alicyclic diisocyanate units contained in the total amount of organic diisocyanate units of a non-alicyclic thermoplastic polyurethane is The combination is 9 0 to 100 moles %, and 9 It is preferably 5 to 100 mol %, particularly preferably 99 to 100 mol %. If the content of the non-alicyclic diisocyanate unit is too low, the compatibility between the non-alicyclic thermoplastic polyurethane and the hygroscopic polymer tends to decrease.

[0028] By using such a molded article of a polyurethane composition as the polishing layer of a polishing pad, a polishing pad can be obtained that has a polishing layer that combines a high polishing rate, high planarization properties, low scratch properties, and excellent dressability.

[0029] In such a molded article of the polyurethane composition, the compatibility between the non-alicyclic thermoplastic polyurethane and the hygroscopic polymer is increased, and thus the dispersibility of the hygroscopic polymer in the molded article is increased. More specifically, the soft segment derived from the polymer diol of the non-alicyclic thermoplastic polyurethane and the hygroscopic polymer are easily compatible. And, when the polishing layer, which is the molded article, absorbs the slurry, the extensibility of the polishing layer is appropriately increased. As a result, the dressing for optimizing the surface roughness of the polishing surface can be completed in a short time.

[0030] On the other hand, the crystalline hard segment derived from the chain extender contained in the non-alicyclic thermoplastic polyurethane and the hygroscopic polymer have low compatibility. Therefore, the crystalline hard segment is easily maintained. As a result, the hardness of the non-alicyclic thermoplastic polyurethane is less likely to decrease. In other words, the hygroscopic polymer has high compatibility with the soft segment and low compatibility with the hard segment.

[0031] As a result, a polishing layer is obtained that is a molded body containing thermoplastic polyurethane that has high extensibility when it contains a hygroscopic polymer and absorbs water, and can maintain high hardness. Such a polishing layer maintains high polishing speed and high flattening ability due to its high hardness of D hardness 75 to 90, and also maintains high dressability due to the extensibility improving effect of the hygroscopic polymer that tends to be unevenly distributed in the soft segment, and low scratchability due to its hydrophilicity.

[0032] The non-alicyclic diisocyanate used in the production of the non-alicyclic thermoplastic polyurethane is a diisocyanate other than an alicyclic diisocyanate, and specifically, is an aromatic diisocyanate or a linear aliphatic diisocyanate that does not have an aliphatic cyclic structure.

[0033] The aromatic diisocyanate is a diisocyanate compound containing an aromatic ring in its molecular structure. Specific examples thereof include 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, m-xylylene diisocyanate, p-xylylene diisocyanate, 1,5-naphthylene diisocyanate, 4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatodiphenylmethane, chlorophenylene-2,4-diisocyanate, and tetramethylxylylene diisocyanate.

[0034] The linear aliphatic diisocyanate is a diisocyanate compound having a linear aliphatic skeleton that does not have a ring structure in the molecular structure. Specific examples thereof include ethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, dodecamethylene diisocyanate, isophorone diisocyanate, lysine diisocyanate, 2,6-diisocyanatomethyl caproate, bis(2-isocyanatoethyl) fumarate, bis(2-isocyanatoethyl) carbonate, and 2-isocyanatoethyl-2,6-diisocyanatohexanoate.

[0035] The non-alicyclic thermoplastic polyurethane can be obtained by using, as the raw material, an organic diisocyanate containing, for example, 60 mol % or more, preferably 90 mol % or more, more preferably 95 mol % or more, particularly preferably 99 mol % or more, and particularly preferably 100 mol % of a non-alicyclic diisocyanate.

[0036] Each non-alicyclic diisocyanate may be used alone or in combination of two or more. Among these, the organic diisocyanate contains aromatic diisocyanate, further 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, and isophorone diisocyanate, and particularly contains 100 mol % of 4,4'-diphenylmethane diisocyanate, in order to obtain a polishing pad with particularly excellent planarization properties.

[0037] In addition, a non-alicyclic diisocyanate may be used in combination with an alicyclic diisocyanate as long as the effect of the present invention is not impaired. The alicyclic diisocyanate is a diisocyanate compound having an alicyclic structure. Specific examples thereof include isopropylidene bis(4-cyclohexyl isocyanate), cyclohexylmethane diisocyanate, methylcyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexene, and the like. If the content of the alicyclic diisocyanate is too high, the compatibility with the hygroscopic polymer tends to decrease, and the planarization property also tends to decrease.

[0038] The polymer diol is a diol having a number average molecular weight of 300 or more, and examples thereof include polyether diol, polyester diol, polycarbonate diol, and polymer diols obtained by combining these.

[0039] Specific examples of polyether diols include poly(ethylene glycol), poly(propylene glycol), poly(tetramethylene glycol), poly(methyltetramethylene glycol), poly(oxypropylene glycol), and glycerin-based polyalkylene ether glycols. These may be used alone or in combination of two or more. Among these, poly(ethylene glycol) and poly(tetramethylene glycol) are preferred because they are particularly compatible with the hard segment of the non-alicyclic thermoplastic polyurethane.

[0040] A polyester diol is a polymeric diol having an ester structure in the main chain, produced by subjecting a dicarboxylic acid or an ester-forming derivative thereof, such as an ester or an anhydride, to a direct esterification reaction or an ester exchange reaction with a low molecular weight diol.

[0041] Specific examples of dicarboxylic acids include aliphatic dicarboxylic acids having 2 to 12 carbon atoms, such as oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecane dicarboxylic acid, 2-methylsuccinic acid, 2-methyladipic acid, 3-methyladipic acid, 3-methylpentanedioic acid, 2-methyloctanedioic acid, 3,8-dimethyldecanedioic acid, and 3,7-dimethyldecanedioic acid; dimerized aliphatic dicarboxylic acids having 14 to 48 carbon atoms (dimer acids) obtained by dimerizing unsaturated fatty acids obtained by fractional distillation of triglycerides, and hydrogenated products thereof (hydrogenated dimer acids); alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, and orthophthalic acid. These may be used alone or in combination of two or more.

[0042] Specific examples of low molecular weight diols include aliphatic diols such as ethylene glycol, 1,3-propanediol, 1,2-propanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol; alicyclic diols such as cyclohexane dimethanol such as 1,4-cyclohexane dimethanol and 1,4-cyclohexane diol; and the like. These may be used alone or in combination of two or more. Among these, low molecular weight diols having 3 to 12 carbon atoms, and more preferably having 4 to 9 carbon atoms, are preferred.

[0043] Polycarbonate diols are obtained by reacting low molecular weight diols with carbonate compounds such as dialkyl carbonates, alkylene carbonates, and diaryl carbonates. Examples of low molecular weight diols include the low molecular weight diols described above. Specific examples of dialkyl carbonates include dimethyl carbonate and diethyl carbonate. Specific examples of alkylene carbonates include ethylene carbonate. Specific examples of diaryl carbonates include diphenyl carbonate.

[0044] Among the polymer diols, polyether diols such as poly(ethylene glycol) and poly(tetramethylene glycol), polyester diols such as poly(nonamethylene adipate)diol, poly(2-methyl-1,8-octamethylene adipate)diol, poly(2-methyl-1,8-octamethylene-co-nonamethylene adipate)diol, and poly(methylpentane adipate)diol, are preferred, and in particular polyester diols containing low molecular weight diol units having 6 to 12 carbon atoms, because they have particularly excellent compatibility with the hard segments derived from the chain extender units of the non-alicyclic thermoplastic polyurethane.

[0045] The number average molecular weight of the polymer diol is 300 or more, more than 300 to 2,000, further 350 to 2,000, particularly 500 to 1,500, and especially 600 to 1,000, since it can maintain high compatibility with the hard segment of the non-alicyclic thermoplastic polyurethane, and thus it is possible to obtain a polishing layer that is particularly unlikely to cause scratches on the polished surface. The number average molecular weight of the polymer diol is a number average molecular weight calculated based on the hydroxyl value measured according to JIS K1557.

[0046] As the chain extender, a chain extender that has been conventionally used in the production of polyurethanes, which is a compound having a molecular weight of 300 or less and having two or more active hydrogen atoms in the molecule capable of reacting with an isocyanate group, is used.

[0047] Specific examples of chain extenders include, for example, ethylene glycol, diethylene glycol, propylene glycol, 2,2-diethyl-1,3-propanediol, 1,2-, 1,3-, 2,3- or 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,4-bis(β-hydroxyethoxy)benzene, 1,4-cyclohexanediol, bis-(β-hydroxyethyl)terephthalate, 1,9-nonanediol, m- or p-xylylene glycol. diols such as ethylenediamine, trimethylenediamine, tetramethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 3-methylpentamethylenediamine, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 1,2-diaminopropanediamine, ,1,3-diaminopropane,hydrazine,xylylenediamine,isophoronediamine,piperazine,o-,m- or p-phenylenediamine,tolylenediamine,xylylenediamine,adipic dihydrazide,isophthalic dihydrazide,4,4'-diaminodiphenylmethane,4,4'-diaminodiphenyl ether,4,4'-bis(4-aminophenoxy)biphenyl,4,4'-bis(3-aminophenoxy)biphenyl,1,4'-bis(4-aminophenoxy)benzene,1,3'-bis(4-aminophenoxy)benzene,1,3 -Bis(3-aminophenoxy)benzene,3,4'-diaminodiphenyl ether,4,4'-diaminodiphenyl sulfone,3,4-diaminodiphenyl sulfone,3,3'-diaminodiphenyl sulfone,4,4'-methylene-bis(2-chloroaniline),3,3'-dimethyl-4,4'-diaminobiphenyl,4,4'-diaminodiphenyl sulfide,2,6'-diaminotoluene,2,4-diaminochlorobenzene,1,2-diaminoanthraquinone,1,4-diaminoanthraquinone,3,3'-diaminobenzophenone,3,Examples of the diamines include 4-diaminobenzophenone, 4,4'-diaminobenzophenone, 4,4'-diaminobibenzyl, R(+)-2,2'-diamino-1,1'-binaphthalene, S(+)-2,2'-diamino-1,1'-binaphthalene, 1,3-bis(4-aminophenoxy)C3-10alkane, 1,4-bis(4-aminophenoxy)C3-10alkane, 1,5-bis(4-aminophenoxy)C3-10alkane, and other 1,n-bis(4-aminophenoxy)C3-10alkanes (n is 3 to 10), 1,2-bis[2-(4-aminophenoxy)ethoxy]ethane, 9,9-bis(4-aminophenyl)fluorene, and 4,4'-diaminobenzanilide. These may be used alone or in combination of two or more.

[0048] Among the chain extenders, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol and 1,4-cyclohexanedimethanol are particularly preferred because they have excellent compatibility with the soft segment derived from the polymer diol unit.

[0049] The molecular weight of the chain extender is 300 or less, and is particularly preferably 60 to 300 from the viewpoint of excellent compatibility between the hard segment and the soft segment.

[0050] The non-alicyclic thermoplastic polyurethane is obtained by reacting a polyurethane raw material containing an organic diisocyanate including a non-alicyclic diisocyanate, a polymer diol, and a chain extender as described above. For the production of the non-alicyclic thermoplastic polyurethane, a known polyurethane synthesis method using a prepolymer method or a one-shot method in which a urethane reaction is performed can be used without any particular limitation. In particular, a method in which a polyurethane raw material is melt-polymerized substantially in the absence of a solvent, particularly a method in which a polyurethane raw material is continuously melt-polymerized using a multi-screw kneading extruder, is particularly preferred in terms of excellent continuous productivity.

[0051] The blending ratio of the polymer diol, organic diisocyanate and chain extender in the polyurethane raw material may be adjusted as appropriate, but it is preferable to blend the various components so that the amount of isocyanate groups contained in the organic diisocyanate is 0.95 to 1.30 mol, preferably 0.96 to 1.10 mol, and particularly 0.97 to 1.05 mol per 1 mol of active hydrogen atoms contained in the polymer diol and chain extender, in order to obtain a polishing layer with excellent mechanical strength and abrasion resistance.

[0052] The mass ratio of the polymer diol, organic diisocyanate and chain extender in the polyurethane raw material (mass of polymer diol:total mass of organic diisocyanate and chain extender) is preferably 10:90 to 50:50, more preferably 15:85 to 40:60, and particularly preferably 20:80 to 30:70.

[0053] The content of nitrogen atoms derived from isocyanate groups in the non-alicyclic thermoplastic polyurethane is preferably 4.5 to 7.5 mass%, further preferably 5.0 to 7.3 mass%, and particularly preferably 5.3 to 7.0 mass%, from the viewpoint of obtaining a polishing layer having appropriate hardness, which exhibits particularly high flattening properties and polishing efficiency on the polished surface, and in which the occurrence of scratches is particularly suppressed.

[0054] As the non-alicyclic thermoplastic polyurethane thus obtained, a thermoplastic polyurethane obtained by reacting a polymer diol such as poly(ethylene glycol), poly(tetramethylene glycol), poly(nonamethylene adipate)diol, poly(2-methyl-1,8-octamethylene adipate)diol, poly(2-methyl-1,8-octamethylene-co-nonamethylene adipate)diol, or poly(methylpentane adipate)diol with an organic diisocyanate such as 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, or 2,6-tolylene diisocyanate, and at least one chain extender selected from the group consisting of 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, and 1,4-cyclohexanedimethanol is preferred because it has excellent light transmittance and therefore makes it easy to adopt a means for optically detecting the amount of polishing in CMP.

[0055] The weight average molecular weight of the non-alicyclic thermoplastic polyurethane is preferably 80,000 to 200,000, more preferably 120,000 to 180,000, in view of particularly excellent compatibility with hygroscopic polymers. The weight average molecular weight is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography.

[0056] The polyurethane composition of the present embodiment may contain a thermoplastic polyurethane that does not contain a non-alicyclic diisocyanate in the organic diisocyanate unit (hereinafter, also referred to as an alicyclic thermoplastic polyurethane) within a range that does not impair the effects of the present invention. When an alicyclic thermoplastic polyurethane is contained, the content of the alicyclic thermoplastic polyurethane in the polyurethane composition is preferably 0 to 9.9% by mass, more preferably 0 to 5% by mass.

[0057] The polyurethane composition of the present embodiment contains a hygroscopic polymer, which has the effect of particularly improving the dressing property of the polishing layer which is a molded article of the polyurethane composition.

[0058] The hygroscopic polymer is defined as a polymer having a moisture absorption rate of 0.1% or more, preferably 0.1-5.0%, more preferably 0.1-3.0%, particularly preferably 0.5-3.0%, and particularly preferably 0.7-2.5%. The moisture absorption rate of the hygroscopic polymer is calculated based on the change in mass when 5.0 g of particles of the hygroscopic polymer to be mixed are thinly spread on a glass dish, left to dry in a hot air dryer at 50°C for 48 hours, and then left to dry under constant temperature and humidity conditions of 23°C and 50%RH for 24 hours. Specifically, the weight (W1) just before treatment under constant temperature and humidity conditions of 23°C and 50%RH and the weight (W2) after treatment under the constant temperature and humidity conditions of 23°C and 50%RH are measured, and the moisture absorption rate is calculated from the following formula. Moisture absorption rate (%)={(W2-W1) / W1}×100

[0059] Examples of such hygroscopic polymers include polymers having a polyalkylene oxide structure, such as a polymethylene oxide structure, a polyethylene oxide structure, a polypropylene oxide structure, a polytetramethylene oxide structure, and a polybutylene oxide structure.

[0060] Specific examples of such hygroscopic polymers include ether-type hygroscopic polymers such as polyethylene oxide (PEO), polypropylene oxide (PPO), PEO-PPO block copolymers, polyester-based thermoplastic elastomers (TPEE), polymethylene oxide alkyl ethers, polyethylene oxide alkyl ethers, polyethylene oxide alkyl phenyl ethers, polyethylene oxide sterol ethers, polyethylene oxide lanolin derivatives, polyethylene oxide-polypropylene oxide copolymers, and polyethylene oxide-polypropylene alkyl ethers; and ether-ester-type hygroscopic polymers such as polyethylene oxide glycerin fatty acid esters, polyethylene oxide sorbitan fatty acid esters, polyethylene oxide sorbitol fatty acid esters, polyethylene oxide fatty acid alkanolamide sulfates polyethylene glycol fatty acid esters, and ethylene glycol fatty acid esters.

[0061] The weight average molecular weight of the hygroscopic polymer is preferably 5,000 to 10,000,000, more preferably 10,000 to 10,000,000, even more preferably 30,000 to 7,000,000, and particularly preferably 70,000 to 4,000,000, in terms of excellent compatibility with the non-alicyclic thermoplastic polyurethane. The weight average molecular weight of the hygroscopic polymer is a value measured by gel permeation chromatography (polystyrene equivalent).

[0062] The hygroscopic polymer improves the dressing property of the polishing layer. The hygroscopic polymer has high compatibility with the soft segment of the non-alicyclic thermoplastic polyurethane. On the other hand, the hygroscopic polymer has low compatibility with the hard segment of the non-alicyclic thermoplastic polyurethane.

[0063] The content of the non-alicyclic thermoplastic polyurethane in the polyurethane composition is 90 to 99.9 mass%, preferably 95 to 99.9 mass%, and further preferably 99 to 99.9 mass%. If the content of the non-alicyclic thermoplastic polyurethane is less than 90 mass%, the flattening property and polishing speed decrease, and if it exceeds 99.9 mass%, the content of the hygroscopic polymer becomes less than 0.1 mass%, and the effect of improving dressability and the effect of reducing scratch occurrence decrease.

[0064] The content of the hygroscopic polymer in the polyurethane composition is 0.1 to 10% by mass, preferably 0.1 to 5% by mass, and more preferably 0.1 to 1% by mass. If the content of the hygroscopic polymer is less than 0.1% by mass, the effect of improving dressability and the effect of reducing scratch occurrence are reduced. If the content of the hygroscopic polymer is more than 10% by mass, the breaking elongation when swollen with water becomes too high, and the dressability tends to decrease.

[0065] The polyurethane composition of the present embodiment may contain additives such as crosslinking agents, fillers, crosslinking accelerators, crosslinking assistants, softeners, tackifiers, antiaging agents, processing assistants, adhesion agents, inorganic fillers, organic fillers, crystal nucleating agents, heat stabilizers, weathering stabilizers, antistatic agents, colorants, lubricants, flame retardants, flame retardant assistants (antimony oxide, etc.), blooming inhibitors, release agents, thickeners, antioxidants, conductive agents, etc., as necessary, within the scope of not impairing the effects of the present invention. Note that since it is preferable that the molded article of the polyurethane composition of the present embodiment is a non-foamed molded article, it is preferable that it does not contain a foaming agent.

[0066] The polyurethane composition is prepared by melt-kneading a compound containing a non-alicyclic thermoplastic polyurethane, a hygroscopic polymer, and other thermoplastic polyurethanes and additives that are blended as necessary. More specifically, the compound is prepared by uniformly mixing the non-alicyclic thermoplastic polyurethane, the hygroscopic polymer, and other thermoplastic polyurethanes and additives that are blended as necessary with a Henschel mixer, a ribbon blender, a V-type blender, a tumbler, or the like, and then melt-kneading the compound with a single-screw or multi-screw kneading extruder, a roll, a Banbury mixer, a Labo Plastomill (registered trademark), a Brabender, or the like. The temperature and kneading time during melt-kneading are appropriately selected depending on the type and ratio of the non-alicyclic thermoplastic polyurethane, the type of melt-kneading machine, and the like. As an example, the melting temperature is preferably in the range of 200 to 300°C.

[0067] The polyurethane composition is molded into a molded article for the polishing layer. The molding method is not particularly limited, but includes a method of extruding or injection molding the molten mixture using a T-die. In particular, extrusion molding using a T-die is preferred because it is easy to obtain a molded article for the polishing layer with a uniform thickness. In this way, a molded article for the polishing layer is obtained.

[0068] It is preferable that the molded body for the polishing layer is a non-foamed molded body, since it has particularly excellent flattening properties due to its high hardness, it has a surface free of pores and therefore no accumulation of polishing debris, thereby reducing the occurrence of scratches, and it has a low wear rate for the polishing layer, allowing it to be used for a long period of time.

[0069] The molded product has a durometer D hardness of 75 to 90, measured with a type D durometer conforming to JIS K 7215 under the condition of a load holding time of 5 seconds. By having such a high hardness, high planarization properties and a high polishing rate are maintained. If the durometer D hardness is less than 75, the polishing layer becomes soft and the polishing efficiency decreases. On the other hand, if the durometer D hardness is 91 or more, scratches are likely to occur.

[0070] In addition, the molded body preferably has a Vickers hardness of 21 or more, since a polishing layer having particularly excellent flattening properties can be obtained. Here, the Vickers hardness is defined as the hardness measured with a Vickers indenter conforming to JIS Z 2244. The upper limit of such Vickers hardness is not particularly limited, but is, for example, 90.

[0071] In addition, when the extensibility of the molded body, particularly when the molded body absorbs a slurry, is high, the polishing surface of the polishing layer is easily roughened, and the dressing property is improved. For this purpose, the molded body has a rupture elongation S1 at saturation swelling when saturated with water at 50°C of 50 to 250%, more preferably 50 to 230%, and particularly preferably 50 to 200%. In addition, the molded body has a rupture elongation S2 at dry at 48 RH% humidity and 23°C of 0.1 to 10%, more preferably 1 to 10%, and particularly preferably 2 to 9%. In addition, it is preferable that the ratio S1 / S2 of the rupture elongation S1 at saturation swelling to the rupture elongation S2 at dry is 20 to 50, since a polishing layer having particularly excellent dressing property and flattening property can be obtained.

[0072] Furthermore, it is preferable that the molded body has a laser light transmittance of 60% or more for a laser wavelength of 550 nm in a 0.5 mm thick sheet when saturated and swollen in water at 50°C, as this makes it easier to reduce the occurrence of scratches and also makes it easier to employ inspection using optical means to determine the polishing end point while polishing the polishing surface of a substrate such as a wafer.

[0073] In addition, the molded product preferably has a storage modulus of 0.1 to 1.0 GPa, more preferably 0.2 to 0.9 GPa, and particularly preferably 0.3 to 0.8 GPa when saturated with water at 50° C., in order to easily maintain higher planarization properties. If the storage modulus is too low when saturated with water at 50° C., the polishing layer becomes soft, and the planarization properties tend to decrease, and the polishing speed tends to decrease. If the storage modulus is too high when saturated with water at 50° C., scratches tend to occur easily.

[0074] Furthermore, the contact angle of the molded article with water is preferably not more than 80 degrees, more preferably not more than 50 degrees, and even more preferably not more than 60 degrees. If the contact angle is too high, scratches may easily occur.

[0075] Next, a polishing pad including such a molded article for a polishing layer as a polishing layer will be described. The polishing pad of this embodiment includes a polishing layer formed by cutting out a piece of a circular shape or the like from the molded article for a polishing layer.

[0076] The polishing layer is manufactured by adjusting the dimensions, shape, thickness, etc. of the molded body for the polishing layer obtained as described above by cutting, slicing, buffing, punching, etc. In addition, it is preferable that recesses such as grooves and holes are formed on the polishing surface of the polishing layer in order to supply the slurry to the polishing surface uniformly and sufficiently. Such recesses are also useful for discharging polishing waste that causes scratches and for preventing damage to the wafer due to adsorption of the polishing pad.

[0077] The thickness of the polishing layer is not particularly limited, but is preferably, for example, 0.8 to 3.0 mm, more preferably 1.0 to 2.5 mm, and particularly preferably 1.2 to 2.0 mm.

[0078] The polishing pad is a polishing pad that includes a polishing layer that is a molded body of the polyurethane composition as described above, and may be a single-layer polishing pad that is made of only a polishing layer, or a multi-layer polishing pad that further includes a cushion layer or the like laminated on the back surface of the polishing layer. When the cushion layer is a layer that has a hardness lower than that of the polishing layer, it is preferable because it can improve polishing uniformity while maintaining dressing property.

[0079] Specific examples of materials used for the cushion layer include composites in which nonwoven fabric is impregnated with polyurethane (e.g., "Suba400" (manufactured by Nitta Haas Corporation)); rubbers such as natural rubber, nitrile rubber, polybutadiene rubber, and silicone rubber; thermoplastic elastomers such as polyester-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, and fluorine-based thermoplastic elastomers; foamed plastics; and polyurethane. Among these, polyurethanes having a foamed structure are particularly preferred because they are likely to provide the flexibility desired for the cushion layer.

[0080] The polishing pad of this embodiment described above is preferably used for CMP. Next, an embodiment of CMP using the polishing pad 10 of this embodiment will be described.

[0081] CMP uses a CMP apparatus 20 equipped with a circular platen 1, a slurry supply nozzle 2 for supplying a slurry 6, a carrier 3, and a dresser 4, as shown in Fig. 1. A polishing pad 10 is attached to the surface of the platen 1 with a double-sided adhesive sheet or the like. The carrier 3 supports a substrate 5 to be polished.

[0082] In the CMP apparatus 20, the platen 1 is rotated, for example, in the direction indicated by the arrow, by a motor (not shown). The carrier 3 is rotated, for example, in the direction indicated by the arrow, by a motor (not shown) while pressing the surface to be polished of the substrate 5 against the polishing surface of the polishing pad 10. The dresser 4 is rotated, for example, in the direction indicated by the arrow.

[0083] When using a polishing pad, prior to or during polishing of a substrate to be polished, the polishing surface of the polishing pad is finely roughened and dressed to form a roughness suitable for polishing. Specifically, a CMP dresser 4 is pressed against the surface of a polishing pad 10 fixed to a platen 1 and rotating while water is flowing on the surface of the polishing pad 10, and the surface of the polishing pad 10 is dressed. As the dresser, for example, a diamond dresser in which diamond particles are fixed to the carrier surface by nickel electrodeposition or the like is used.

[0084] The type of dresser is preferably diamond grit #60-200, but can be appropriately selected according to the resin composition of the polishing layer and the polishing conditions. The dresser load, which depends on the diameter of the dresser, is preferably 5-50N when the diameter is 150mm or less, 10-250N when the diameter is 150-250mm, and about 50-300N when the diameter is 250mm or more. The rotation speed of the dresser and the platen is preferably 10-200rpm, but it is preferable that the rotation speed of the dresser and the platen is different to prevent synchronization of rotation.

[0085] In the case of a polishing pad having a high hardness polishing layer, it is difficult to make the polishing surface of the polishing layer sufficiently rough. Also, it may take time to form a roughness suitable for polishing. Also, it may take time to break in the surface of an unused polishing pad. With the polishing pad of this embodiment, the polishing surface becomes sufficiently rough and the dressing time is also shortened.

[0086] In the polishing pad of this embodiment, it is preferable to form a rough surface with an arithmetic surface roughness Ra of 4.0 to 8.0 μm, more preferably 4.2 to 8.0 μm. If the arithmetic surface roughness is low and dressing is insufficient, the polishing surface is difficult to hold the slurry sufficiently, and the polishing rate tends to decrease. In addition, if the arithmetic surface roughness Ra is too high, there is a concern that the surface layer of the polishing pad will be in solid contact with the polishing surface of the polishing substrate, and scratches will easily occur.

[0087] After the dressing is completed, the polishing of the surface of the substrate is started. In the polishing, a slurry 6 is supplied from a slurry supply nozzle 2 to the surface of the rotating polishing pad. The slurry contains, for example, a liquid medium such as water or oil; an abrasive such as silica, alumina, cerium oxide, zirconium oxide, silicon carbide; a base, an acid, a surfactant, an oxidizing agent, a reducing agent, a chelating agent, etc. In addition, when performing CMP, a lubricating oil, a coolant, etc. may be used together with the slurry as necessary. Then, the substrate to be polished, which is fixed to a carrier and rotates, is pressed against the polishing pad with the slurry evenly spread over the polishing surface. Then, the polishing is continued until a predetermined flatness and polishing amount are obtained. The finishing quality is affected by adjusting the pressing force applied during polishing and the speed of the rotation of the platen and the relative movement of the carrier.

[0088] The polishing conditions are not particularly limited, but in order to perform polishing efficiently, the rotation speed of each of the platen and the substrate to be polished is preferably low, 300 rpm or less. In addition, the pressure applied to the substrate to be polished in order to press the substrate against the polishing surface of the polishing pad is preferably 150 kPa or less from the viewpoint of preventing scratches after polishing. In addition, during polishing, it is preferable to continuously or discontinuously supply the slurry to the polishing pad so that the slurry is evenly distributed on the polishing surface.

[0089] After polishing, the substrate is thoroughly washed and then dried using a spin dryer or the like to remove any water droplets adhering to the substrate, resulting in a smooth polished surface.

[0090] The CMP of this embodiment is preferably used for polishing in the manufacturing process of various semiconductor devices, MEMS (Micro Electro Mechanical Systems), etc. Examples of the object to be polished include semiconductor substrates such as silicon, silicon carbide, gallium nitride, gallium arsenide, zinc oxide, sapphire, germanium, diamond, etc.; insulating films such as silicon oxide film, silicon nitride film, low-k film, etc. formed on wiring boards having predetermined wiring, wiring materials such as copper, aluminum, tungsten, etc.; glass, quartz, optical substrates, hard disks, etc. The polishing pad of this embodiment is particularly preferably used for polishing insulating films and wiring materials formed on semiconductor substrates. EXAMPLES

[0091] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples in any way.

[0092] First, the hygroscopic polymers used in this example are summarized below.

[0093] <Hygroscopic polymer> Polyethylene oxide with a weight average molecular weight of 30,000 (PEO30,000); Moisture absorption rate 0.7% (range 0.1-3.0%) Polyethylene oxide (PEO100,000) with a weight average molecular weight of 100,000; moisture absorption rate of 0.5% Polyethylene oxide (PEO1,000,000) with a weight average molecular weight of 1,000,000; moisture absorption rate of 1.6% (range 0.1-3.0%) Polyethylene oxide with a weight average molecular weight of 7,000,000 (PEO7,000,000); moisture absorption rate of 2.5% (range 0.1-3.0%) Polyethylene oxide-propylene oxide block copolymer (PEO-PPO100,000) with a weight average molecular weight of 100,000; moisture absorption rate of 0.7% (range 0.1-3.0%) Polyethylene oxide-propylene oxide block copolymer (PEO-PPO1,000,000) with a weight average molecular weight of 1,000,000; moisture absorption rate of 1.3% (range 0.1-3.0%) Weight average molecular weight 7,000,000 polyethylene oxide-propylene oxide block copolymer (PEO-PPO7,000,000); Moisture absorption rate 2.1% (range 0.1-3.0%) Thermoplastic polyester elastomer (TPEE); Moisture absorption rate 1.2% (range 0.1-3.0%)

[0094] <Acrylonitrile-styrene copolymer> Acrylonitrile-styrene copolymer; moisture absorption rate 0.08%

[0095] The moisture absorption rate of the polymer was measured as follows.

[0096] 5.0 g of particles of each polymer were thinly spread on a glass dish and left to dry in a hot air dryer at 50°C for 48 hours. Then, the particles were left to dry under constant temperature and humidity conditions of 23°C and 50%RH for 24 hours. The weight (W1) just before the treatment under the constant temperature and humidity conditions of 23°C and 50%RH and the weight (W2) after the treatment under the constant temperature and humidity conditions of 23°C and 50%RH were measured and calculated using the following formula.

[0097] Moisture absorption rate (%)={(W2-W1) / W1}×100

[0098] A production example of the polyurethane used in this example is shown below.

[0099] [Production Example 1] A blend was prepared by blending poly(ethylene glycol) having a number average molecular weight of 600 [abbreviation: PEG], 1,4-butanediol [abbreviation: BD], 1,5-pentanediol [abbreviation: MPD], and 4,4'-diphenylmethane diisocyanate [abbreviation: MDI] in a mass ratio of PEG:BD:MPD:MDI of 15.2:14.2:8.0:62.6.

[0100] The blend was then continuously fed to a twin-screw extruder rotating coaxially by a metering pump, and the molten blend was continuously extruded into water in the form of strands, which were then chopped into pellets by a pelletizer. In this way, non-alicyclic thermoplastic polyurethane I was produced by continuous melt polymerization of the polyurethane raw material. Non-alicyclic thermoplastic polyurethane I contains 100 mol % of MDI, which is a non-alicyclic diisocyanate unit, in the total amount of organic diisocyanate units. The weight average molecular weight of non-alicyclic thermoplastic polyurethane I was 120,000. The pellets obtained were then dehumidified and dried at 70°C for 20 hours.

[0101] [Production Example 2] A blend was prepared by blending poly(tetramethylene glycol) having a number average molecular weight of 850 [abbreviation: PTMG], 1,4-butanediol [abbreviation: BD], 1,5-pentanediol [abbreviation: MPD], and 4,4'-diphenylmethane diisocyanate [abbreviation: MDI] in a ratio of PTMG:BD:MPD:MDI mass ratio of 10.2:15.7:8.8:65.3. A non-alicyclic thermoplastic polyurethane II was produced by continuous melt polymerization of polyurethane raw materials in the same manner as in Production Example 1, except for using this blend. The non-alicyclic thermoplastic polyurethane II contains 100 mol % of MDI, which is a non-alicyclic diisocyanate unit, in the total amount of organic diisocyanate units. The weight average molecular weight of the non-alicyclic thermoplastic polyurethane II was 120,000. The pellets obtained were then dehumidified and dried at 70°C for 20 hours.

[0102] [Production Example 3] A blend was prepared by blending poly(ethylene glycol) having a number average molecular weight of 600 [abbreviation: PEG], 1,4-butanediol [abbreviation: BD], 1,5-pentanediol [abbreviation: MPD], and hexamethylene diisocyanate [abbreviation: HDI] in a ratio such that the mass ratio of PEG:BD:MPD:HDI was 11.6:16.5:9.3:62.6. A non-alicyclic thermoplastic polyurethane III was produced by continuous melt polymerization of polyurethane raw materials in the same manner as in Production Example 1, except that this blend was used. The non-alicyclic thermoplastic polyurethane III contains 100 mol % of HDI, which is a non-alicyclic diisocyanate unit, in the total amount of organic diisocyanate units. The weight average molecular weight of the non-alicyclic thermoplastic polyurethane III was 120,000. The pellets obtained were then dehumidified and dried at 70° C. for 20 hours.

[0103] [Production Example 4] A blend was prepared by blending poly(ethylene glycol) having a number average molecular weight of 600 [abbreviation: PEG], 1,4-butanediol [abbreviation: BD], 1,5-pentanediol [abbreviation: MPD], and isophorone diisocyanate [abbreviation: IPDI] in a ratio such that the mass ratio of PEG:BD:MPD:IPDI was 15.2:14.2:8.0:62.6. Except for using this blend, the polyurethane raw materials were continuously melt-polymerized in the same manner as in Production Example 1 to produce alicyclic thermoplastic polyurethane IV. The alicyclic thermoplastic polyurethane IV contains 100 mol % IPDI, which is an alicyclic diisocyanate unit, in the total amount of organic diisocyanate units. The weight average molecular weight of the alicyclic thermoplastic polyurethane IV was 120,000. The pellets obtained were then dehumidified and dried at 70°C for 20 hours.

[0104] [Production Example 5] A blend was prepared by blending poly(ethylene glycol) having a number average molecular weight of 600 [abbreviation: PEG], 1,4-butanediol [abbreviation: BD], 1,5-pentanediol [abbreviation: MPD], and cyclohexane methyl isocyanate [abbreviation: CHI] in a ratio of PEG:BD:MPD:CHI mass ratio of 15.2:14.2:8.0:62.6. Except for using this blend, the polyurethane raw material was continuously melt-polymerized in the same manner as in Production Example 1 to produce alicyclic thermoplastic polyurethane V. The alicyclic thermoplastic polyurethane V contains 100 mol % of CHI, which is an alicyclic diisocyanate unit, in the total amount of organic diisocyanate units. The weight average molecular weight of the alicyclic thermoplastic polyurethane V was 120,000. The obtained pellets were then dehumidified and dried at 70°C for 20 hours. As the cyclohexane methyl isocyanate, 1,3-Bis(isocyanatomethyl)cyclohexane (Takenate 600, registered trademark, manufactured by Mitsui Chemicals, Inc.) was used.

[0105] [Example 1] The non-alicyclic thermoplastic polyurethane I was charged into a small kneader and melt-kneaded under the conditions of a temperature of 240°C, a screw rotation speed of 100 rpm, and a kneading time of 1 minute. Then, PEO100,000 was added to the small kneader so that the mass ratio of the non-alicyclic thermoplastic polyurethane I:PEO100,000 was 99.5:0.5, and further melt-kneaded under the conditions of a temperature of 240°C, a screw rotation speed of 60 rpm, and a kneading time of 2 minutes. Further melt-kneaded under the conditions of a temperature of 240°C, a screw rotation speed of 100 rpm, and a kneading time of 4 minutes.

[0106] The obtained molten mixture was then left to dry in a vacuum dryer at 70°C for 16 hours or more. The dried molten mixture was then sandwiched between metal plates and placed in a heat press molding machine to melt the molten mixture at a heating temperature of 230°C for 2 minutes, and then heated under a gauge pressure of 40 kg / cm. 2 After cooling them at room temperature, a molded body having a thickness of 2.0 mm that was sandwiched between the hot press molding machine and the metal plate was taken out.

[0107] The obtained molded body having a thickness of 2.0 mm was heat-treated at 110°C for 3 hours, and then cut into a rectangular test piece having a size of 30 mm x 50 mm. The test piece was then cut into a concentric groove (width 1.0 mm, depth 1.0 mm, groove interval 6.5 mm). A recess was formed in a circular molded body of non-alicyclic thermoplastic polyurethane I having a thickness of 2.0 mm to accommodate the test piece, and the test piece was fitted into the recess to obtain a polishing layer of a non-foamed molded body for evaluation. The evaluation was performed as follows.

[0108] [Durometer D hardness of molded product] Using a type D durometer conforming to JIS K 7215 (HARDNESS-TESTER manufactured by Shimadzu Corporation), the type D durometer hardness of the molded body having a thickness of 2.0 mm was measured under the condition of a load holding time of 5 seconds.

[0109] [Vickers hardness of green body] The Vickers hardness of the 2.0 mm thick molded body was measured using a Vickers hardness tester conforming to JIS Z2244 (HARDNESS-TESTER MVK-E2, manufactured by Akashi Corporation).

[0110] [Breaking elongation when dry and breaking elongation of molded body when saturated with 50°C water] Instead of the 2.0 mm thick molded body, a 0.3 mm thick molded body was produced. Then, a No. 2 type test piece (JIS K7113) was punched out from the 0.3 mm thick molded body. Then, the No. 2 type test piece was conditioned for 24 hours at a humidity of 48 RH% and 23°C. Then, a tensile test was performed on the conditioned No. 2 type test piece using a precision universal testing machine (Autograph AG5000 manufactured by Shimadzu Corporation) to measure the breaking elongation. The tensile test was performed under the conditions of a chuck distance of 40 mm, a tensile speed of 500 mm / min, a humidity of 48 RH%, and 23°C. The breaking elongation of five No. 2 type test pieces was measured, and the average value was taken as the breaking elongation S2 (%) when dry. Meanwhile, the No. 2 type test piece was saturated and swollen with 50°C water by immersing it in 50°C warm water for two days. The breaking elongation of the No. 2 test piece that had been swelled to saturation was measured in the same manner, and the breaking elongation S1 at saturation swelling when swelled to saturation in water at 50° C. was determined.

[0111] [Storage modulus E' of molded body when saturated with water at 50°C] Instead of the 2.0 mm thick molded body, a 0.3 mm thick molded body was produced. The 0.3 mm thick molded body was heat-treated at 110°C for 3 hours, and then a 30 mm x 5 mm rectangular mold was used to punch out a test piece for evaluating the storage modulus. The test piece for evaluating the storage modulus was saturated and swollen with 50°C water by immersing it in 50°C warm water for 2 days. The storage modulus E' of the molded body when saturated and swollen with 50°C water was obtained by measuring the dynamic viscoelasticity at 70°C with a measurement range of -100 to 180°C and a frequency of 11.0Hz using a dynamic viscoelasticity measuring device [DVE Rheospector (trade name, manufactured by Rheology Co., Ltd.)]. The storage modulus E' of the two test pieces was measured, and the average value was taken as the storage modulus E' (GPa).

[0112] [Light transmittance of molded body when saturated with 50℃ water] Instead of the 2.0 mm thick molded body, a 0.5 mm thick molded body was produced. The 0.5 mm thick molded body was heat treated at 110°C for 3 hours, and then cut into a 10 mm x 40 mm rectangle by cutting. The test piece was immersed in 50°C warm water for 2 days to swell to saturation with 50°C water, and water droplets on the surface were wiped off. The light transmittance of the test piece of the molded body at a wavelength of 550 nm was measured under the following conditions using an ultraviolet-visible spectrophotometer (Shimadzu Corporation's "UV-2450"). Light source: Laser wavelength (550nm) WI lamp: 50W Distance between detector head and output head: 10cm Test piece measurement position: Midway between the detector head and the output head

[0113] [Dressability (arithmetic surface roughness Ra)] The polishing layer for evaluation was set on the platen of a CMP device (FREX300, manufactured by Ebara Corporation). Then, using a diamond dresser with diamond grit #100 (Asahi Diamond Corporation), the surface of the polishing layer was dressed for 10 minutes under the conditions of a dresser rotation speed of 100 rpm, a turntable rotation speed of 70 rpm, and a dresser load of 40 N while flowing the slurry at a rate of 150 mL / min. Then, the arithmetic surface roughness Ra of the surface of the polishing layer after dressing was measured with a surface roughness measuring instrument (SJ-210, manufactured by Mitutoyo Corporation).

[0114] [Polishing characteristics evaluation] The polishing layer for evaluation was set on the platen of a CMP device (FREX300, manufactured by Ebara Corporation). Then, using a diamond dresser (Asahi Diamond Corporation) with diamond grit #100, the surface of the substrate to be polished was polished under the conditions of a dresser rotation speed of 100 rpm, a turntable rotation speed of 70 rpm, and a dresser load of 40 N while flowing a slurry (Klebosol®, manufactured by DuPont Corporation) at a speed of 200 mL / min. As the substrate to be polished, "SEMATECH764 (manufactured by SKW Associates)" was used, which was a silicon substrate on which a TEOS film (tetra ethoxy silane film) was laminated to a thickness of 3000 nm. CMP was performed under the above conditions, and the difference between the convex part and the concave part (hereinafter also referred to as the remaining step) was measured as an index of planarization using a precision step gauge (Dektak XTL, manufactured by Bruker Corporation) for the part where the pattern with a width of 250 μm (50% density) was continuous. In addition, when the remaining step is 40 nm or less, further 35 nm or less, particularly 33 nm or less, it is judged to have high planarization. Similarly, the polishing speed was evaluated by measuring the polishing time until the film remaining on the convex portion becomes less than 50 nm. In addition, when the polishing time is 150 sec or less, further 145 sec or less, it is judged to have high polishing speed.

[0115] Then, using a wafer defect inspection device (SP-3 manufactured by KLA-Tencor Corporation), the number of scratches larger than 0.21 μm on the entire surface of the polished substrate after polishing was counted. If the number of scratches was less than 30, it was determined that the occurrence of scratches was suppressed.

[0116] The results are shown in Table 1 below.

[0117] [Table 1]

[0118] [Examples 2 to 15, Comparative Examples 1 to 6]

[0119] The properties of the molded article or the polishing layer were evaluated in the same manner as in Example 1, except that the type of polyurethane composition was changed to the composition shown in Table 1 or Table 2. The results are shown in Table 1 or Table 2 below.

[0120] [Table 2]

[0121] Referring to Table 1, all of the polishing pads obtained in Examples 1 to 15 according to the present invention had a large surface roughness Ra and excellent dressability. In addition, the residual step was small and the planarization was excellent. In addition, the polishing time was short and a high polishing rate was obtained. Furthermore, the occurrence of scratches was small. Thus, the polishing pad according to the present invention had a high polishing rate, high planarization, low scratching, and excellent dressability. On the other hand, the polishing pads obtained in Comparative Examples 1 and 2, which did not contain a hygroscopic polymer, had a significantly low surface roughness. In addition, the polishing pads obtained in Comparative Examples 3 to 5, in which the proportion of thermoplastic polyurethane containing a non-alicyclic diisocyanate unit was less than 90% by mass, also had a significantly low surface roughness. In addition, the polishing pad obtained in Comparative Example 5, which contained more than 10% by mass to 20% by mass of a hygroscopic polymer, had a large residual step and poor planarization. Furthermore, the polishing pad obtained in Comparative Example 6, which contained 1 mass % of an acrylonitrile-styrene copolymer with a moisture absorption rate of 0.08% instead of the hygroscopic polymer, also had low surface roughness and large residual steps. [Explanation of symbols]

[0122] 1 Platen 2 Slurry supply nozzle 3. Career 4. Dresser 5 Substrate to be polished 6. Slurry 10 Polishing Pad 20 CMP equipment

Claims

1. A polishing pad comprising a polishing layer which is a molded body of a polyurethane composition, The polyurethane composition contains 90 to 99.9% by mass of a thermoplastic polyurethane containing a non-alicyclic diisocyanate unit as an organic diisocyanate unit, and 0.1 to 10% by mass of a hygroscopic polymer having a moisture absorption rate of 0.1% or more, The thermoplastic polyurethane contains 90 to 100 mol % of at least one of the non-alicyclic diisocyanate units selected from a 2,4'-diphenylmethane diisocyanate unit, a 4,4'-diphenylmethane diisocyanate unit, and a hexamethylene diisocyanate unit, based on the total amount of the organic diisocyanate units; The hygroscopic polymer includes at least one selected from polyethylene oxide (PEO), polypropylene oxide (PPO), a PEO-PPO block copolymer, a polyester-based thermoplastic elastomer, and a polyethylene oxide-polypropylene oxide copolymer; The polishing pad is characterized in that the molded body has a D hardness of 75 to 90, measured with a type D durometer conforming to JIS K 7215 under the condition of a load holding time of 5 seconds.

2. 2. The polishing pad according to claim 1, wherein the thermoplastic polyurethane contains 90 to 100 mol % of 4,4'-diphenylmethane diisocyanate units, which are non-alicyclic diisocyanate units, based on the total amount of the organic diisocyanate units.

3. 2. The polishing pad according to claim 1, wherein the polyurethane composition contains 99 to 99.9% by mass of the thermoplastic polyurethane and 0.1 to 1% by mass of the hygroscopic polymer.

4. 2. The polishing pad according to claim 1, wherein the molded body has a breaking elongation at saturated swelling of 50 to 250% when saturated with water at 50°C.

5. 5. The polishing pad according to claim 4, wherein the molded body has a breaking elongation in a dry state at a humidity of 48 RH% and 23° C. of 0.1 to 10%.

6. The molded body has a breaking elongation at saturated swelling S 1 and the breaking elongation S 2 Comparison with S 1 / S 2 The polishing pad according to claim 5, wherein the n is 20 to 50.

7. 2. The polishing pad according to claim 1, wherein the molded article has a laser light transmittance of 60% or more at a wavelength of 550 nm when a sheet having a thickness of 0.5 mm is saturated and swollen in water at 50°C.

8. 2. The polishing pad according to claim 1, wherein the molded body has a Vickers hardness of 21 or more.

9. 2. The polishing pad according to claim 1, wherein the molded body has a storage modulus of 0.1 to 1.0 GPa when saturated and swollen in water at 50°C.

10. The polishing pad according to any one of claims 1 to 9, wherein the molded body is a non-foamed molded body.

Citation Information

Patent Citations

  • Chemical mechanical polishing pad and chemical mechanical polishing method using the same

    JP2011151373A

  • Polishing pad, manufacturing method of polishing pad, method for polishing surface of polishing object, and method for reducing scratches when polishing surface of polishing object

    JP2019155507A

  • Polishing pad and method for manufacturing polished product

    JP2021053748A

  • Chemical mechanical polishing pad

    WO2007089004A1

  • Chemical mechanical polishing pad and chemical mechanical polishing method using same

    WO2012077592A1